A new bee species of the subgenus Ceratina (Rhysoceratina) (Hymenoptera: Apidae) from northernmost South America - Nathalia A. Flórez-Gómez; Terry Griswold (Revista Mexicana de Biodiversidad)
The subgenus Ceratina (Rhysoceratina) Michener has been known largely from southern South America, registered in Argentina, Paraguay, Uruguay and southern Brazil, with a single species, C. (Rhysoceratina) nitidifrons, from the Eastern Llanos of Colombia. Here we describe and illustrate females and males of a new species, Ceratina (Rhysoceratina) macondiana sp. nov. It is apparently endemic to the Caribe Region of Colombia and Venezuela, extending the distribution range of Rhysoceratina to the extreme north of South America. Ceratina macondiana sp. nov. is easily separable from other Rhysoceratina species in both sexes by the color of the marginal cell, which is darker than the rest of the forewing and the dense white hairs on the lateral sides of the propodeum and posterior ridge of the scutellum.